MANAJEMEN SEBAGAI PARADIGMA PEMBANGUNAN DALAM MEWUJUDKAN GOOD GOVERNANCE - Sugiyarti, Sri Riris (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT One of main causes for multicrisis in Indonesia are mismanagement and moral hazard problem in every sektors. Political situation and economy is a two sides which linked each other. So far, executives in government mostly see politics and economy as the effort to gain power for individuals or groups, fully ignoring the essential task for manager to maintain the country using good management principles which will enable to rise sustainable value of creation. Keywords: Good governance, political paradigm, management paradigm, economic development.